Ethno medicinal, phytochemical and pharmacological aspects of solanum incanum (lin.) - Mwonjoria, John K.; Ngeranwa, Joseph J.; Kariuki, Hellen N.; Githinji, Charles G.; Sagini, Micah N.; Wambugu, Stanley N. (International Journal of Pharmacology and Toxicology, 2014)
Solanum incanum is used in Africa and other parts of world as a folklore remedy for various ailments that include; sore throat, angina, stomach ache, ear inflammation, snake bites, wounds, liver disorders, skin ailments (ringworm), warts, inflammatory conditions, painful periods and fever. Phytochemical studies of this herb indicate that it contains substances such as steroidal alkaloids, glyco-alkaloids, antioxidants (flavonoids and chlorogenics), saponins and even carcinogenic substances. The herbal extract posses’ antinociceptive, antipyretic, anti-spasmolytic, orexic, anorexic, hypoglycemic, antimicrobial, anti-schistosomal, anti-fungal, and anti-cancer activity. The herb is therefore likely to be a major source of novel, affordable and effective therapeutic substances against myriad ailments afflicting people in the world. This review explores the phyto-pharmacological effects of the S. incanum and compiles vital information that may assist researchers on what is known about this herb and gaps for further investigation. Keywords: Anticancer, Antimicrobial, Antinociceptive, Antipyretic, Solanum Incanum.